2012
DOI: 10.3892/ijo.2012.1362
|View full text |Cite
|
Sign up to set email alerts
|

Yin Yang-1 inhibits tumor cell growth and inhibits p21WAF1/Cip1 complex formation with cdk4 and cyclin D1

Abstract: Abstract. The GLI-Krüppel zinc finger factor yin yang-1 (YY1) is a complex protein that regulates a variety of processes including transcription, proliferation, development and differentiation. YY1 inhibits cell growth in a cell typespecific manner. The role played by YY1 in its control of tumor cell growth is unclear and controversial. We show here that YY1 can suppress the growth of different tumor cell types in vitro, including human breast carcinoma cells and glioblastoma cells. YY1 also blocked the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…14,15 It has been reported that YY1 has an effect on the proliferation of tumor cells (such as breast carcinoma cells, glioblastoma cells) and plays an inhibitory role. 16 However, the effect of YY1 on the proliferation of pancreatic cancer remains unclear.…”
mentioning
confidence: 99%
“…14,15 It has been reported that YY1 has an effect on the proliferation of tumor cells (such as breast carcinoma cells, glioblastoma cells) and plays an inhibitory role. 16 However, the effect of YY1 on the proliferation of pancreatic cancer remains unclear.…”
mentioning
confidence: 99%
“…Studies have shown YY1 positively regulated expression of several oncogenes, such as c-Myc and c-Fos[ 35 ]. In addition, YY1 can positively regulate some tumor suppressor genes, such as p21 and p16[ 36 , 37 ]. However, one study showed that YY1 was a negative cell growth regulator by inhibiting c-Myc function[ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…YY1 is a zinc finger protein and a member of the GLI-Kruppel family that can activate or inactivate gene expression depending on its interacting partners (136), YY1 is overexpressed in multiple cancer types and correlates with poor clinical outcomes (137,138). However, other papers report that YY1 inhibits the cell growth in different tumor cell types in vitro, including human breast carcinoma cells and glioblastoma cells (139).…”
Section: Mitochondrial Biogenesis and Mitophagy: Mtorc1 In Cancermentioning
confidence: 99%